PENGARUH PUPUK ORGANIK CAIR DARI BONGGOL PISANG TERHADAP KADAR HARA NITROGEN TOTAL DAN C-ORGANIK PADA BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) - Ingrid Ovie Yosephine; Zulham Effendi; Widya Tri Lestari (Jurnal Agro Estate, 2021)
Suspension media is made of natural ingredients to multiply microorganisms that can accelerate the destruction of organic matter. Banana hump contains water, iron, phosphorus, calcium, carbohydrates, calories and protein, which are potential as organic fertilizers. Application of banana weevil fertilizer is expected to increase the carrying capacity of the soil for the availability of organic matter and nutrients. The purpose of this study was to determine the best concentration or dose of organic liquid fertilizer for banana weevil on the vegetative growth of oil palm (Elaeis guineensis Jacq.) seedlings in the Main Nursery. Based on this statement, this research was compiled with the object of oil palm in the Main Nursery. This research was conducted in the Nursery Practice Garden area at STIP-AP Medan. Soil analysis was carried out at the Soil Laboratory of the Agricultural Technology Research Institute (BPTP) of North Sumatra. The time of the study was carried out for 8 months, from January 2021 - August 2021. This study used a Randomized Block Design (RAK) with 2 factors, namely Factor (1) Liquid Organic Fertilizer Banana Cobs and Factor (2) Compound Fertilizer (NPK) 16:16 :16. The treatment was repeated 3 times, with the number of samples being 2 plants so that the sample population was 54 plants. Parameters observed were seedling height, stem circumference, number of leaves, leaf width, root wet weight, shoot wet weight, shoot dry weight, root dry weight, total nitrogen nutrient content and C-organic nutrient content. The data obtained were analyzed statistically by analysis of variance (ANOVA) with 5% and 1% significant difference tests. The results showed that the treatment of banana weevil liquid organic fertilizer and compound fertilizer had no significant effect on the observed parameters. However, the biomass formed was significantly affected as indicated by the weight parameter. The availability of total nitrogen and C-organic nutrients in Ultisol soil showed a very low classification with total nitrogen values of 0.07 – 0.09% and C-organic values of 0.22 – 0.54%.